2016
DOI: 10.1038/srep31595
|View full text |Cite
|
Sign up to set email alerts
|

Surface-anchored poly(acryloyl-L(D)-valine) with enhanced chirality-selective effect on cellular uptake of gold nanoparticles

Abstract: Chirality is one of the ubiquitous phenomena in biological systems. The left handed (L-) amino acids and right handed (D-) sugars are normally found in proteins, and in RNAs and DNAs, respectively. The effect of chiral surfaces at the nanoscale on cellular uptake has, however, not been explored. This study reveals for the first time the molecular chirality on gold nanoparticles (AuNPs) functions as a direct regulator for cellular uptake. Monolayers of 2-mercaptoacetyl-L(D)-valine (L(D)-MAV) and poly(acryloyl-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 50 publications
(60 reference statements)
1
31
1
Order By: Relevance
“…For instance, almost all of amino acids (except glycine) in proteins are “left-handed” ( l -), while all sugars in DNA and RNA are “right-handed” ( d -) [ 16 ]. Our and other previous studies have demonstrated chirality-dependent nature of cellular uptake [ 17 ], cell adhesion [ 18 ], cell differentiation [ 19 , 20 ], protein adsorption [ 21 , 22 ] (i.e., amount and affinity) and cytotoxicity [ 23 ] on flat substrates or nanoparticles coated with chiral molecules. More recently, two studies observed that NPs with surface-anchored chiral molecules could modulate the autophagy [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, almost all of amino acids (except glycine) in proteins are “left-handed” ( l -), while all sugars in DNA and RNA are “right-handed” ( d -) [ 16 ]. Our and other previous studies have demonstrated chirality-dependent nature of cellular uptake [ 17 ], cell adhesion [ 18 ], cell differentiation [ 19 , 20 ], protein adsorption [ 21 , 22 ] (i.e., amount and affinity) and cytotoxicity [ 23 ] on flat substrates or nanoparticles coated with chiral molecules. More recently, two studies observed that NPs with surface-anchored chiral molecules could modulate the autophagy [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 89%
“…Gold(III) chloride hydrate (HAuCl 4 ) and sodium citrate (C 6 H 5 Na 3 O 7 ·2H 2 O) were purchased from Sinopharm group Co. Ld. Poly(acryloyl- l -valine) ( l -PAV) ( M w 4926 Da, polydispersity 1.24), poly(acryloyl- d -valine) ( d -PAV) ( M w 4997 Da, polydispersity 1.15) were synthesized and were characterized according our previous works [ 17 , 23 ]. High glucose dulbecco’s modified eagle medium (DMEM) and fetal bovine serum (FBS) were obtained from HyClone (USA).…”
Section: Methodsmentioning
confidence: 99%
“…Chiral discrimination in response to homochiral biological systems has been frequently reported in the literature. 23,24 Herein, NO release catalyzed by samples with different surface chiralities was evaluated using a Sievers 280i chemiluminescence analyzer. A steady and continuous NO release was observed when the samples were pushed into endogenous NO donor solution (Fig.…”
Section: Discrimination In Catalyzing No Release On Different Chiral mentioning
confidence: 99%
“…12 Selective behaviour is also displayed by chiral gold nanoparticles coated with poly(acryloyl-L-valine)-b-poly(2-hydroxyethyl methylacrylate) (L)-PAV-b-PHEMA or its D counterpart in A549 and HepG2 cancer cells. 13 It has been found that magnetic nanoparticles decorated with L-phosphotyrosine (L-pY) are innocuous to cells while D-pY-decorated ones selectively inhibit cancer cells. 14 Recently, graphene quantum dots functionalized with chiral biomolecules have been reported as new efficient selective antimicrobial nanoagents.…”
Section: Introductionmentioning
confidence: 99%